PENGARUH LATIHAN SENAM AEROBIK â€œLOW INTENSITYâ€ SELAMA 1 (SATU) JAM TERHADAP PENURUNAN GLUKOSA DALAM DARAH PADA ANGGOTA SANGGAR SENAM PUSKESMAS KAMPAR KIRI TENGAH DESA SIMALINYANG KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Tonamal, Toni; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the observation that researchers do in local goverment clinicMiddle East Kampar of the interview, the researcher found the reason they followed thegymnasium to practice at the same time maintaining the health of the disease whichavoid one diabetes and obsitas. The aim of this study was to investigate the effect ofaerobic exercise "Low Intensity" for one (1) hour to determine the decrease in glucosein the blood at the local goverment clinic gym member Simalinyang Village Middle EastKampar District of Kampar. This type of research is an experimental research. Thepopulation in this study are member local goverment clinic gym Simalinyang VillageMiddle East Kampar District of Kampar aim to 15 people in total. On the basis of thecalculation results obtained two normally distributed random test data. Calculationsusing the t-test obtained t-value of 2.55. Once obtained, the t-value, is the next step tothe value of the table t. T table at n = 15 or df = 14, with a standard deviation of 5%was 2.14. The results of the comparison between the value of t with t arithmetic table itis obtained that t> t table or 2,55> 2,14. The conclusion of this study is there Effects ofaerobic exercise "Low Intensity" for 1 (one) hour to the decrease in glucose in the bloodat the local goverment clinic gym member Simalinyang Village Middle East KamparDistrict of Kampar. From this research it is known that aerobic exercise low intensityfor 1 hour to give effect to a decrease in blood glucose , therefore the researcherssuggest that gymnastics aerobic low intensity may continue to be applied 2 or 3 times aweek in order to keep blood glucose levels and maintain body fitness participantsexercise.Keyword : Low intensity aerobikc, Glucose In The Blood